Comparative analysis of adaptability and stability of soybean genotypes for cultivar registration and protection - A. P. L. Costa; A. C. R. Moitinho; A. P. Silva; L. O. Amaral; J. S. Souza; S. H. Unêda-Trevisoli (Brazilian Journal of Biology)
Abstract One of the challenges for genetic and plant breeding is the selection of genotypes that are increasingly adapted, productive, and stable to the cultivation environments, without losing the desired agronomic traits. These evaluations are important for determining the ideal genotypes for each environment. Without these evaluations, the behavior of cultivars or genotypes cannot be predicted, affecting performance, and causing losses for farmers. This work aimed to characterize, by different methodologies, the agronomic performance, adaptability, and stability of soybean genotypes in a preliminary trial, to select the superior genotypes, aiming at the Registration and Protection of Cultivars. The experiment was conducted in the field in a randomized block design with two replications, where 50 soybean genotypes were evaluated, including 3 checks, during two agricultural, two different environments. Agronomic traits were evaluated: number of days to maturity, number of days to flowering, plant height at maturity, the weight of a thousand grains, lodging, oil content, and grain yield. To determine the adaptability and productive stability of the genotypes, GGE biplot multivariate prediction methodologies and REML/BLUP mixed models were used and compared, using the main agronomic traits of production and oil content, which are of industrial importance in human and animal nutrition. The methods of the analysis showed differences regarding the ordering of adaptability and stability, however, they were unanimous in considering the genotypes as superior: 24; 29; 30; 32; 34, and 42 for yield and 4; 17; 37, and 44 for oil content. The predominant pedigree of the selected genotypes consists of bi-parental crosses, except genotype 24, which comes from a quadruple cross.